Surveillance of hepatocellular carcinoma in cirrhotic patients: Current knowledge and future directions - DEMİRTAŞ, COŞKUN ÖZER; ÖZDOĞAN, OSMAN CAVİT (My University, 2020)
Patients with cirrhosis are at the highest risk to develop hepatocellular carcinoma (HCC), with a variable annual risk of 1-8%. Currently, biannual abdominal ultrasound (USG) with or without alpha fetoprotein (AFP) is the recommended HCC surveillance strategy of major professional liver societies for all cirrhotic patients. However, the effectiveness of USG and AFP has been a sprawling subject of debate due to conflicting results and the low quality of the evidence. The role of cross-sectional imaging is controversial due to potential harm and cost-effectiveness concerns. Several novel serum biomarkers have been introduced for HCC screening, but have yet to be validated for various geographic regions. A risk-stratified algorithm is needed to increase the yield of HCC surveillance by distinguishing a high-risk group that requires more intense screening with cross-sectional imaging and serum biomarkers, and a low-risk group, where the standard surveillance strategy is continued. In this review, the strengths and concerns related to standard USG-based surveillance strategy are discussed, as well as efforts to increase the effectiveness of surveillance.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; Cirrhosis complications; hepatocellular carcinoma; surveillance